Optimasi Tablet Hancur di Mulut Metoklopramida Menggunakan Sari Tape Padat dan Pati Jagung - SAMRAN SAMRAN; KARSONO KARSONO; M.T SIMANJUNTAK; JANSEN SILALAHI (Fakultas Farmasi Universitas Pancasila, 2013)
The preparation of brewed white sticky rice extract or brem from white glutinous rice had been researched by using variation concentration of yeast. The yeasts were bought from traditional market without trade mark. Tape extract obtained by squeezed tape mass using a pressurized equipment, water of tape obtained further filtered using a 60 mesh sieve and the waste is disposed. The variation of yeast influences the pH of liquid tape extract. The optimum concentration of yeast was 1,5%. The research of orally disintegrating tablet (ODT) that using direct compress method was designed by using Simplex Lattice Design (SLD) mixture design programme with two components mixture: brewed white sticky rice extract and corn starch (CS), and metochlopramide as model drug. Brewed white sticky rice extract and CS were formulated become nine designs of formula. Brewed white sticky rice extract was dominant increasing flow and compactability of ODT mass, but decreasing wetting time, disintegrating time and dissolution rate. CS was dominant increasing wetting time, disintegrating time, water absorption ratio and dissolution rate. The optimum ODTs formula was brewed white sticky rice extract (20%) and CS (80%) with flow (8,68±1,72 sec), hardness (2,15±0,14 kg), wetting time (40,00±1,67 sec), disintegrating time (36±10,07 sec), disintegrating time in oral cavity (46,17±2,23 sec) and dissolution rate (0,172 mg/sec).